2020
DOI: 10.21873/cgp.20195
|View full text |Cite
|
Sign up to set email alerts
|

NONO Is a Negative Regulator of SOX2 Promoter

Abstract: Background/Aim: Sex determining region Y (SRY)box 2 (SOX2) is a transcription factor essential for the maintenance of proliferation and self-renewal of cancer stem cells and is associated with breast cancer initiation. Regulation of cancer stem cell plasticity by SOX2 requires both positive and negative SOX2 transcription factors, but the negative regulator is still largely unknown. Materials and Methods: SOX2 promoter-binding proteins were identified by liquid chromatography-mass spectrometry/mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These genes possess features that well contribute to the definition of specific characteristics of DHSF-BR16 cells. It has been recently demonstrated that SOX2, a transcription factor essential for the maintenance of proliferation and self-renewal of cancer stem cells, is related to breast cancer initiation 49 . YAP1, the core protein of the Hippo signaling pathway, has been associated with malignancy and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…These genes possess features that well contribute to the definition of specific characteristics of DHSF-BR16 cells. It has been recently demonstrated that SOX2, a transcription factor essential for the maintenance of proliferation and self-renewal of cancer stem cells, is related to breast cancer initiation 49 . YAP1, the core protein of the Hippo signaling pathway, has been associated with malignancy and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%